Grotesque and Southern Gothic in Cormac McCarthy’s Blood Meridian - Hüseyin Altındiş (Selçuk Üniversitesi Edebiyat Fakültesi Dergisi)
This article offers a post-southernist reading that challenges and problematizes the impacts of haunted past of the American South with implications of violence embodied by Judge Holden in Cormac McCarthy’s Blood Meridian, or The Evening Redness in the West. In order to present a moral compass to the reader, the text presents good-evil dichotomy and the world of human through the uncanny and grotesque characters of “the kid” and “the judge.” Through this dichotomy, the reader acknowledges the possibility of alternative narratives that escape from the control and totalizing gaze of dominant power and discourses. The counter- narratives complicate any types of subjugation, mythologized history, and refuse to approve the violence that the prevailing power practices against innocent people. This paper aims to analyze the struggle between the good and evil and the degree of insanity performed by the evil depicted through southern gothic and grotesque scenes. Thus, the paper contributes to grotesque reading of the selected text through a number of elements: “exaggeration, hyperbolism, and excessiveness,” generally considered fundamental attributes of the grotesque style (Bakhtin, 1984, p. 303).